Civil & Structural Engineering. Seismic design of Building & Bridges - WILLIAMS, Alan (Kaplan, 2004)
Containing everything civil and structural engineers need to prepare for the seismic design topics of the Structural Engineering I and II exams, this guide emphasizes methods that lead to the quickest and simplest solution to any problem. In addition to exam preparation, this book is an outstanding reference manual for practicing engineers and upper-level engineering students.